Developing communicative competence in L2 tertiary level students: remarks on culturally responsive teaching - Zybert, Jerzy; Lehman, Iga (Scripta Neophilologica Posnaniensia, 2019)
Semiotic links exist among communication, culture, teaching, and learning and this has important implications for implementing culturally responsive teaching. The present paper provides some arguments in favour of creating culturally sensitive classrooms where students have an opportunity to acquire a broader cultural awareness which helps them to develop their intercultural communicative competence.